BERPIKIR MATEMATIS SISWA PADA PEMBELAJARAN AUDIO VISUAL BERBANTUAN LKPD BERBASIS LITERASI NUMERASI - Panglipur, Indah Rahayu; Rosita, Merlinda (Universitas Tanjungpura, 2023)
This research is to find out students' mathematical thinking processes in visual audio learning with the help of student worksheets based on numeracy literacy on coordinate material. with a qualitative-descriptive subject of 30 grade 7 students at a junior high school in Jember. The research instrument is a matter of description and student results sheets are concluded from learning. The aim is to know the process of thinking mathematically in students. Descriptive data analysis based on the results of the LKPD sheet answers. Given math questions whose answers do not only use numbers, but also with descriptive sentences that are explained correctly and according to theory. the use of audio-visual learning media, students understand more about the direct example material presented in the learning video. The video also presents examples or benefits of coordinates that are usually used in everyday life, for example in airplane flights